Sistem pendukung keputusan untuk evaluasi kinerja pegawai honorer dengan metode weighted product - Lia, Lia Umbari Putri; Yesputra, Rolly (Universitas Muhammadiyah Riau, 2024)
Evaluating the performance of contractual employees is a crucial step to ensure operational effectiveness and efficiency within government institutions, including at the Wali Nagari Binjai Office. However, manual evaluation processes often face challenges such as subjectivity and inaccuracy. This study aims to develop a Decision Support System (DSS) based on the Weighted Product (WP) method to provide an objective and transparent solution for evaluating the performance of contractual employees. The WP method was selected for its capability to process multi-criteria data by considering the weights of relevant criteria, such as work discipline, productivity, and attendance. The web-based system automates the calculation of preference values for each employee, simplifying the management process of identifying top performers efficiently. System testing results indicate that this approach produces more accurate evaluations compared to manual methods, with an accuracy rate of up to 90% based on historical data. Additionally, the system is user-friendly and can be integrated with other management processes. This study not only provides practical contributions to the Wali Nagari Binjai Office but also offers a model that can be adapted by other government institutions.